A Simple, Reusable and Low-Cost LVDT-Based in Situ Bolt Preload Monitoring System during Fastening for a Truck Wheel Assembly - Shin Jang; Juhyun Nam; Samgon Lee; Je Hoon Oh (Metals, 2019)
The aim of this study is to design and test a new, simple, and reusable linear variable differential transformer (LVDT)-based in situ bolt preload monitoring system (L-PMS) during fastening of a truck wheel assembly. Instead of measuring the elongation of a bolt, the distance between the end surfaces of both the bolt and nut was monitored via the L-PMS. The distance obtained from the L-PMS was experimentally correlated with the actual preload measured by a washer-type load cell. Since the variation of the distance is related to the stiffness of the bolt and clamped parts, a finite element analysis was also conducted to predict the sensitivity of L-PMS. There was a strong linear relationship between the distance and bolt preload after the bolt and nut were fully snugged. However, a logarithm-shaped nonlinear relationship was irregularly observed before getting snugged, making it difficult to define a clear relationship. In order to tackle this issue, an arc-shaped conductive line was screen-printed onto the surface of the clamped parts using a conductive carbon paste. The results show that a resistance variation of the conductive line during fastening enables to determine the snug point, so the L-PMS combined with resistance measurement results in an approximately ±6% error in the measurement of bolt preload. The proposed L-PMS offers a simple but highly reliable way for measuring bolt preload during fastening, which could be utilized in a heavy-truck production line.